Peran Manajemen Metadata Dalam Meningkatkan Kualitas dan Tata Kelola Data - Lubis, Novri Salsabilla; Nasution, Muhammad Irwan Padli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the era of digital transformation and data-driven decision making, data quality and governance are key factors in determining the operational effectiveness and competitive advantage of an organization. Unfortunately, many organizations still face challenges in managing data that is scattered, unstandardized, and lacks adequate documentation. This is where the role of metadata becomes crucial. Metadata, as descriptive information about data, not only facilitates understanding of the context and structure of data, but also supports the management of the data life cycle as a whole. This study aims to identify and analyze the strategic role of metadata management in improving data quality and supporting the implementation of effective data governance. The method used is a literature study of various scientific journals, international standards, and best practices in metadata management. In addition, a conceptual analysis was carried out on the relationship between metadata attributes and data quality dimensions such as accuracy, consistency, completeness, and recency. The results of the analysis show that good metadata management directly contributes to increased transparency, efficiency of cross-system data integration, reduced risk of errors, and compliance with data regulations such as GDPR or PP No. 71 of 2019 concerning Electronic Systems and Transactions in Indonesia. With a centralized metadata repository supported by clear organizational policies, data can be controlled, tracked, and utilized optimally.